EVALUASI PELAKSANAAN PROGRAM BERAS UNTUK KELUARGA MISKIN DI KELURAHAN KISARAN BARU KECAMATAN KISARAN BARAT KABUPATEN ASAHAN - CITRA Gustianda (Welfare StatE, 2013)
Poverty is a root cause that we can not ignore in Indonesia. With a soaring population figures in Indonesia, with the need to live more and more sharply. Economic crisis in Indonesia that the government has a role to any matters arising and destabilize society, the view that poverty is the beginning of a surge in population numbers. Government hereby makes the program a program of rice to poor families or shortened by Raskin. The program aims to reduce poverty and on the basis of the fulfillment of the right to food needs of poor communities. This research study was held in the village of Kisaran Baru sub-district Kisaran Barat Regency Asahan as one of the locations of rice research program for poor families who are often referred to with Raskin. Research study using descriptive method with qualitative approach. To obtain necessary data, this research study using data collection technique and field study which consists of questionnaire, interview and observation. The conclusions obtained throught analysis of the data that The Evalution of implementation program of rice to poor families in the village of Kisaran Baru sub-district Kisaran Barat Regency Asahan is implementation of good. The calculation result is implementation of good viewied from several measurements that have been made, input as of 0,273 from process as of 0,64 from output as of 0,683 and from impact 0,37. Keywords :evaluation, implementation, raskin.